The halloween effect in european equity mutual funds - Curto, J. D. (2018)
Bouman and Jacobsen (2002) documented the existence of a calendar anomaly in stock market returns, which they call the Halloween effect, based on the fact that the returns during the months of May to October tend to be lower than returns during the months of November to April. Following closely the methodology used by Bouman and Jacobsen (2002), we investigate the presence of the Halloween effect in the European Equity Mutual Funds from 1997 to 2013. We conclude that: i) the Halloween Effect is statistically and economically significant; ii) this effect has disappeared after the Bouman and Jacobsen publication; iii) this anomaly might be due to the negative average returns during the months of May to October, rather than a higher performance during the period from November to April; and iv) an investment strategy based on this anomaly clearly beats the classical buy and hold strategy.